DIGITALISASI MEDIA PEMBELAJARAN BAHASA INGGRIS KEPERAWATAN BERBASIS E-BOOK DALAM MENINGKATKAN HASIL BELAJAR MAHASISWA DI STIKES YAPIKA MAKASSAR - Bustang, Bustang; Fansury, Andi Hamzah; Rahman, Ali Wira (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The development of technology is one of the factors that participate in influencing the behavior of students in learning. In this study, the author tries to create an interesting learning media for students and can be used not only during class hours but wherever and whenever they can access it. One of the media that can be used is E-book. This study uses Research and Development using the ADDIE Model. The population and sample of this study were Nursing Students STIKES YAPIKA Makassar in the 2020/2021 academic year. The development procedure is divided into five stages, namely 1) Analysis stage in the form of literature study and field study and needs analysis, 2) Design stage, 3) Development stage, 4) Implementation stage and 5) Evaluation stage. Research data were collected using documentation and questionnaires which were analyzed descriptively and inferential statistics through SPSS version 22 for Windows. It is hoped that from the results of this study, lecturers can apply or use learning media that are in accordance with the times, namely E-books that can be accessed by students not only in class but anywhere and anytime. With the E-book-based learning media, it is hoped that student literacy culture can also increase